A facile method for the isolation of porcine heart mitochondrial malate dehydrogenase by affinity elution chromatography on Procion Red HE3B. Issue 11 (November 1983) - Smith, Keith; Sundaram, Trichur K.
Abstract : A quick, simple method has been devised for isolating pig heart mitochondrial malate dehydrogenase in apparently homogeneous state and good yield. It entails the adsorption of the enzyme to agarose-linked Procion Red HE3B and specific elution of a ternary complex consisting of the malate dehydrogenase, NAD +, and L-malate.